2020
DOI: 10.3389/fcimb.2020.580088
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of the Parasite Enterocytospora artemiae From Chinese Grass Shrimp (Palaemonetes sinensis)—First Report in Asia

Abstract: Chinese grass shrimp (Palaemonetes sinensis) is an economically important crustacean in Chinese aquaculture. Recently, we found that shrimp in Panjin city were infected with microsporidia, a group of fungi. The hepatopancreas of several infected shrimp showed white turbidity and pathological changes that negatively affected the health and appearance of the shrimp. Histopathology and transmission electron microscopy were used to examine the development of the parasite within its parasitophorous vacuole. Our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 42 publications
1
13
0
1
Order By: Relevance
“…Meanwhile, the qPCR method was used to detect EAM tissue tropism and the carriers in the culture environment. The tissue tropism detection found that the content in the hepatopancreas was the highest, indicating that it was the main location of EAM, which was consistent with previous research (Rode et al, 2013;Jiang et al, 2020). At the same time, EAM was also detected in the gut, gill, stomach and muscle, and the same results have been obtained with EHP (Santhoshkumar et al, 2017;Cheng et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Meanwhile, the qPCR method was used to detect EAM tissue tropism and the carriers in the culture environment. The tissue tropism detection found that the content in the hepatopancreas was the highest, indicating that it was the main location of EAM, which was consistent with previous research (Rode et al, 2013;Jiang et al, 2020). At the same time, EAM was also detected in the gut, gill, stomach and muscle, and the same results have been obtained with EHP (Santhoshkumar et al, 2017;Cheng et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…MT 645708) had 94% shared homology with the SSU rRNA gene of Globulispora mitoporans (GenBank No. KT762153), which shared more than 85% identity with five other species (Jiang et al, 2020). Therefore, we selected a specific target to modify the SYBR Green I qPCR detection method to detect microsporidia in P. sinensis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations